Numerical Study of Turbidity Current over a Three-Dimensional Seafloor (Communications in Computational Physics, 2018)
Turbidity current over a Gaussian-bump is investigated numerically usingthe upwinding combined compact difference (UCCD) scheme and the immersed boundary (IB) method in Cartesian grids. In the prediction of lock-exchange gravity-drivenflow motion, the initial discontinuous concentration field is smoothed to avoid numerical oscillation by solving the Hamilton-Jacobi equation. The UCCD spatial schemewith sixth-order accuracy which introduces less dispersion errors is then used to discretize advection and diffusion terms in the calculation of concentration transportequation. Direct forcing IB method is employed to treat solid object bumps in the fluidflow. The incompressible Navier-Stokes solutions are obtained through the projectionmethod. Analysis of the smoothing procedure, grid sensitivity and the effect of theSchmidt numbers is performed for the turbidity current problem to validate the proposed numerical algorithm, which is shown to be capable of accurately demonstratingtheir results. Finally, several problems of turbidity current over a three-dimensionalseafloor are investigated. The front locations of the currents interacting with the bumpare predicted under different Reynolds numbers. Also, the current properties, namelythe suspended particle mass, sedimentation rate and energy budget, are comparedwith the available numerical results.